DIGITALISASI PEMASARAN UMKM KERIPIK PISANG-SINGKONG DI KALIGLAGAH: PENDEKATAN ABCD DAN DAMPAK PADA OMZET - Jannah, Nur; Wahidah, Nur; Qadariyah, Lailatul (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This community service program aims to improve the production capacity, digital marketing, and economic performance of banana and cassava chip MSMEs in Kaliglagah Village through digital interventions based on Asset-Based Community Development (ABCD). Twelve MSMEs received mentoring for six months (February–September 2025). At baseline, production capacity ranged from 40–70 packages per day, with an average turnover of IDR 3,050,000 (median IDR 3,000,000; range IDR 2,450,000–IDR 3,800,000). The interventions included packaging improvements, mobile photography, copywriting, a content calendar, and the activation of four digital channels (Instagram, Facebook, WhatsApp Business, and marketplaces). Changes in turnover were calculated as percentages, raw material prices were recorded from weekly records, and monitoring was carried out through sales logs, transaction receipts, and a dashboard. Results show production capacity increased to 80–120 packs per day, turnover increased by 29.9% (≈30%), and non-village buyers increased from <5% to 34%. Digital analytics: reach 7,200 accounts/month, 12,000 impressions, 3.2% CTR, and conversion 2.8–3.1%. Upstream impact: banana prices increased from IDR 3,800/kg to IDR 4,350/kg, and cassava from IDR 2,400/kg to IDR 2,760/kg (≈15%). These findings confirm the effectiveness of low-cost, locally-asset-based digitalization for rural food MSMEs, expanding markets and supporting supply chains.